Application of Titanate Nanotubes for Photocatalytic Decontamination in Water: Challenges and Prospects - Ji, Haodong; Ni, Jinren; Zhao, Dongye; Liu, Wen (ACS ES&T Engineering, 2022)
Photocatalysis is an efficient technology for water decontamination and purification. Development of photocatalysts with high activity becomes the key to this research area. In recent years, titanate nanotubes (TNTs), derived from TiO2 nanoparticles through hydrothermal treatment with NaOH/KOH, have been attracting great attention. TNTs are composed of edge-sharing [TiO6] octahedrons as the skeleton and Na+/H+/K+ in the interlayers, which exhibit a uniform tubular microstructure, a large specific surface area, high photoelectric conversion properties, and good stability. Therefore, TNTs and their modified materials are widely used for removal of heavy metals and organic contaminants through photocatalytic oxidation or reduction. In this perspective, we systematically summarize cutting-edge research on the application of TNT-based photocatalysts in the water treatment area, illustrate the challenges for fundamental research and practical applications, and reveal the critical knowledge gaps and research needs for the future. In particular, preparation and specific properties of TNT-based photocatalysts are presented. Modification of TNTs to promote photocatalytic activity is discussed as well as their applications for contaminants removal from water. The latest advances in theoretical calculations on materials and contaminants in this photocatalysis system are clarified. In the future, strategic programs on both fundamental research and practical applications of TNT-based photocatalysts are proposed.